Taxonomic study of Lebinthus Stål, 1877 (Orthoptera: Gryllidae: Eneopterinae) with description of six new species in the Philippines - Baroga-Barbecho, Jessica B.; Tan, Ming Kai; Yap, Sheryl A.; Robillard, Tony (Zootaxa, 2020)
The genus Lebinthus Stål, 1877 (Orthoptera: Gryllidae: Eneopterinae: Lebinthini) in the Philippines is studied. New locality records are provided for L. bitaeniatus Stål, L. sanchezi Bolívar, L. polillensis Baroga, Yap & Robillard, L. puyos Robillard, and L. luae Robillard & Tan. Six new species are described from Mt. Porras, Sibalom (L. dannybaletei sp. nov.), Mt. Balatukan, Misamis Oriental (L. parvus sp. nov.), Mt. Empagatao, Misamis Oriental (L. palaceus sp. nov.), Tarumpitao, Palawan (L. hamus sp. nov.), Mt. Malinao, Albay (L. magayon sp. nov.), and Boracay, Aklan (L. boracay sp. nov.). A distribution map, a taxonomic key, and an updated checklist of the genus in the Philippines are also provided.